Evaluating the Measurement of Activated Sludge Foam Potential. - FRYER, MARTIN; O'FLAHERTY, EOGHAN; GRAY, NICHOLAS (My University, 2011)
The most widely used technique for assessing the propensity of activated sludge to suffer from biological foaming is to measure foam potential. This involves measuring the amount of foam produced from sludge under conditions of controlled aeration. Two approaches have been adopted: (1) Air is passed through specially designed columns from fine porous diffusers at a fixed rate to form uniform sized bubbles or (2) employing Alka-Seltzer? tablets which effervesce when added to the sludge. Both tests generate foam formation which can then be quantified. Foam assessment in activated sludge is reviewed. A sintered disc aeration column was compared with the Alka-Seltzer? test method and both methods examined under a range of different environmental conditions. Foam potential measured by the sintered disc method displayed better repeatability compared to the Alka-Seltzer test. The use of a wire cage placed over the tablets greatly improved the precision of the Alka-Seltzer test. A positive linear correlation was also found between foam potential and temperature (4?20 ?C). Sludge solids concentration was also shown to influence foaming potential making comparisons between reactors problematic. Recommendations on how to improve the repeatability of foam potential measurements are given.
PUBLISHED
Keywords: Botany; Sludge Foam; Smart & Sustainable Planet